Mini Ensiklopedis : Telaah Perusahaan Pembiayaan - Mu'awwanah, Uliyatul; Mu’awanah, Mu’awanah; Masfiah, Alifatul; Cahyono, Dimas Nur; Ulum, Libasul; Misrul, Misrul; Nafisa, Yusro (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2024)
In the midst of the soaring business world which is increasingly popular, especially in the community and even among various groups, both young and old, it is necessary to realize that all forms of risk are certain and need to be minimized in the smooth running of the business, one of which is the capital or funding factor which is the support in business start up. So the purpose of this discussion or article is to examine the role of finance companies so that they are able to provide more alternatives for the development of the business sector as well as the various facilities offered in expanding the provision of financing. The importance of this discussion topic is as a reference for humans especially Muslims to be able to understand matters relating to finance companies within the scope of sharia economics.